Time to Breathe - Asylum seeker's refugee centre to Helsinki - Virkkala, Inari (2011)
Inari Virkkala's master's thesis is a concept and design for a new asylum seeker's reception centre in Helsinki. The work is partly based on the author's work in the City of Helsinki Social Services Department 1.5. - 31.11.2010, but the thesis is an independent, academic project. The Social Services Department has four reception centres in Helsinki. The oldest of the centres, the Kyläsaari centre founded in 1996, is structurally at the end of its life span and would require an expensive renovation. However, this is not reasonable as the new Kalasatama area will be expanded on the current site of the centre in 2020s. The City of Helsinki is currently working to determine the best possible option for the new centre. The thesis presents the process of the consideration of the solution for the replacement of the Kyläsaari centre. The introductory chapter analyses the national and international processes contributing to the design of the new centre. In the first chapter, a new spatial plan for the centre is specified. In the second chapter, alternative options for the concept of the new centre are evaluated. The third chapter presents a renovation plan for Sofianlehto B-building. During the process, the author interviewed asylum seekers in two of the reception centres. These interviews, transcribed by the author, are highlighted with colour throughout the thesis. As the first larger groups of asylum seekers arrived to Finland during the recession in the beginning of 1990s, the attitudes towards the asylum seekers were quite negative and this has cast, and is still casting, it's shadow on the design of the asylum seeker's reception centres. Currently, the living conditions in the four existing asylum seeker's reception centres in Helsinki do not meet the goals set for a humane housing in contemporary Finland. The conditions for housing in the transit-centres in Helsinki can be quite basic as the living time in the centres is aimed to be shortest possible. According to the residents, the housing conditions are causing ...